Предмет: Математика,
автор: вооыо
помогите пожалуйста решить ;)
Приложения:
Ответы
Автор ответа:
2
1) раскрываем скобки
а² + ас +ав+вс = а² + а(в +с) +вс
а² +(ас + ав) + вс = а² + а(в+с) + вс
а² + а(с+в) + вс = а²+ а(в+с) +вс
2)
а² - ас - ав+вс = а² - а(в + с) +вс
а² -(ас + ав) + вс = а² - а(в+с) + вс
а² - а(с+в) + вс = а² - а(в+с) +вс
а² + ас +ав+вс = а² + а(в +с) +вс
а² +(ас + ав) + вс = а² + а(в+с) + вс
а² + а(с+в) + вс = а²+ а(в+с) +вс
2)
а² - ас - ав+вс = а² - а(в + с) +вс
а² -(ас + ав) + вс = а² - а(в+с) + вс
а² - а(с+в) + вс = а² - а(в+с) +вс
Похожие вопросы
Предмет: Алгебра,
автор: kendinada0
Предмет: Математика,
автор: Katanatw
Предмет: География,
автор: pavel01071981
Предмет: Математика,
автор: ErnestReve
Предмет: Математика,
автор: Infalible